Assessment of COVID-19 prevention practice and associated factors in Jimma town, Ethiopia: A mixed study - Bedane, Deriba; Abdissa, Daba; Leta, Bati; Gerema, Urge; Lomboro, Abraham; Kune, Guta; Neme, Abiru; Kene, Kumsa; Berhanu, Nimona; Dubiwak, Abebe Dukessa; Tareke, Kasahun Girma (Frontiers in Public Health, 2022)
Background: The coronavirus disease 2019 (COVID-19) affected the mental and physical well-being, social structure, countries’ economy as well as individuals and community resilience, trust, and inequalities among the societies. Almost all activities have been returned to the pre-Cona era, despite the emergence of new strains and the spread of the disease. Hence, this study was conducted to assess COVID-19 prevention practice and the associated factors. Materials and methods: A community-based cross-sectional study triangulated with the qualitative findings was conducted. A total of 422 sample households were involved in the quantitative study. The quantitative data were collected using a structured questionnaire and 12 key informants were interviewed for the qualitative part. The quantitative data was processed and entered into the Epi Data version 4.6 and analyzed using SPSS 26.0. Similarly, the qualitative data were analyzed using ATLASti.7.1.04 software package. Descriptive statistics and binary logistics regression (p<0.25) were conducted to identify the candidate variable for multivariable logistics regression analysis (p<0.05) 95% confidence interval was used to establish the level of significance of the variables with the practice. Results: Interviews were conducted with a total of 422 participants, yielding a response rate of 100%. Good preventive practices were 13.3% among the respondents. Age ≥ 50 years, [AOR=2.85, 95%, CI=1.24-6.53], being recovered from COVID-19, [AOR=2.41, 95%, CI=1.18-4.92], having chronic diseases [AOR=3.70, 95%, CI=1.88-7.25] and living with COVID-19 high risk [AOR=2.96, 95%, CI=1.47-5.991 were independently associated with good preventive practices. Conclusions: In this study, it was understood that there were poor COVID-19 preventive practices in the study setting. There was a disparity in adherence to the preventive practices in relation to (i.e., 50 and above years), the experience of contracting COVID-19 and living with the high-risk group above 65 years old. In addition, the community had different misconceptions or risk perceptions related to COVID-19 infection and preventive practices. This highlights the need to design health education programs and implement risk and/or social and behavior change communication interventions to change perceptions or misconceptions of people to bring about the desired behavior change and prevent the spread of COVID-19.